2021
DOI: 10.7827/turkishstudies.46241
|View full text |Cite
|
Sign up to set email alerts
|

Goal Orientation, Need for Achievement and Meaning: Psychobiographical Investigation of Füreya Koral

Abstract: Psychobiography studies focus on the lives of historically important people in their socio-cultural context based on various psychological theories. In present psychobiography the motives and motivational processes of an artist were examined by utilizing the concepts of goals, goal orientation, processes of goal setting, need for achievement and need for meaning. Five methodological steps of psychobiography were followed. (1) Fureya Koral who was a pioneering ceramic artist of Republican Era of Turkey and bega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
0
0
0
Order By: Relevance
“…These studies examined different historical figures in different disciplines, in different theoretical frameworks. The findings of the study showed that psychobiography studies in our country are carried out in various scientific fields such as Turkish Language and Literature (Erbay, 2021), Psychology (Harlak et al, 2021), Theology (Gürsu, 2015(Gürsu, , 2020Kaplan, 2009), Social Work and Counseling (Aktu, 2018;Aktu, Varol and Sevim, 2018), Education (Turna, 2020) and History (Genç and Genç, 2016). It has been observed that the historically significant people discussed in the studies examined vary.…”
Section: Extended Summarymentioning
confidence: 92%
See 1 more Smart Citation
“…These studies examined different historical figures in different disciplines, in different theoretical frameworks. The findings of the study showed that psychobiography studies in our country are carried out in various scientific fields such as Turkish Language and Literature (Erbay, 2021), Psychology (Harlak et al, 2021), Theology (Gürsu, 2015(Gürsu, , 2020Kaplan, 2009), Social Work and Counseling (Aktu, 2018;Aktu, Varol and Sevim, 2018), Education (Turna, 2020) and History (Genç and Genç, 2016). It has been observed that the historically significant people discussed in the studies examined vary.…”
Section: Extended Summarymentioning
confidence: 92%
“…When the results about which aspects of the lives of historical people were examined, it was concluded that there were variables such as goal orientation, need for success and meaning, death anxiety, melancholy, religious identity, and psychosocial development. When the methodologies used by the studies were examined, it was seen that only one study (Harlak et al, 2021) was carried out by following the methodological steps suggested in the literature.…”
Section: Extended Summarymentioning
confidence: 99%